A Review on the Energy prospects of Indian Remote Islands and Preliminary assessment of Marine Current Energy Potential. Issue 1 (December 2020) - Vyshnavi, P.; Samad, A.; Venkatesan, N.; Avital, E.J.
Abstract: The islands in the Indian Ocean as other remote islands are often challenged to meet their energy needs, and constantly getting electricity from the mainland is expensive. In this article, the present scenario and future prospects of the energy sources for all the Indian islands are discussed. Data collected from different buoys of INCOIS are analysed, and a location near Minicoy has been chosen for further study. This paper also provides the preliminary analysis of marine current energy feasibility in that location.